LEARNING ENGLISH AT SCHOOLS IS CRUCIAL IN TODAY’S GLOBALIZED WORLD FOR SEVERAL REASONS - Raximov Mansur Odiljonovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: It is presented in the article about all possible opportunities that knowing foreign languages can create for a speaker. The value of mastering English language is explained and discussed in details. The most appropriate stage of everyone’s life is a school time.